Virtual Inertia Optimization Allocation Based On Grey Wolf Algorithm - Genzhu Wu; Dongliang Nan; Yu Duan; Lu Zhang; Ziming Zhu; Xiqiang Chang (淡江理工學刊, 2024)
To address the optimal allocation of virtual inertia as a replacement for rotating inertia in power systems, this paper proposes a virtual inertia optimal allocation method. First, the calculation method for determining the minimum inertia requirement of power systems with high penetration of renewable energy is clarified. Next, considering factors like frequency stability and virtual inertia investment costs, a virtual inertia optimization allocation model is constructed with the goals of minimizing the frequency security index and investment costs, subject to constraints such as critical inertia, rate of change of frequency, and maximum frequency deviation. And the grey wolf algorithm is utilized to solve this model. Finally, the modified WSCC 9-bus system and IEEE 39-bus system are simulated to validate the effectiveness and universality of the proposed model in optimally allocating virtual inertia while balancing frequency stability and investment costs.